A comparison of test-retest reliability of four cognitive screening tools in people with dementia. Issue 15 (17th July 2022) - Lee, Ya-Chen; Lin, Yi-Te; Chiu, En-Chi
Abstract: Purpose: This study aimed to compare the test-retest reliability and minimal detectable change (MDC) of the Mini-Mental State Examination (MMSE), the Short Portable Mental Status Questionnaire (SPMSQ), the Montreal Cognitive Assessment (MoCA), and the Saint Louis University Status Examination (SLUMS) in a single sample of people with dementia. Methods: Sixty people with dementia were assessed twice two weeks apart, and the test-retest reliability was examined using the intraclass correlation coefficient (ICC) for four screening tools. The MDC95 value was calculated based on the standard error of measurement to estimate the random measurement error. Results: The ICC values for screening tools were 0.86–0.90. The MDC95 values (MDC95 %) were 5.0 (17.2%), 2.74 (27%), 4.71(20%), and 6.26 (24%) for the MMSE, SPMSQ, MoCA, and SLUMS, respectively. Conclusions: Overall, the four screening tools were similar in test-retest reliability which imply that the MMSE, MoCA, SPMSQ, and SLUMS were reliable in monitoring cognitive function in people with dementia. The results of the direct comparisons of test-retest reliability of the four screening tools provide useful information for both clinicians and researchers to select an appropriate cognitive screening tool. Implications for Rehabilitation: The MMSE, MoCA, SPMSQ, and SLUMS are equally reliable and thus they could be used to monitor the cognitive function in people with dementia. The MDC values are useful in determining whether a real change has occurred between repeated assessments for people with dementia.